COMPARATIVE STUDY OF SEVEN BRANDS OF LEVOFLOXACIN 500 MG FILM-COATED TABLET MARKETED IN YEMEN - Othman, Gamil Q.; Al-Worafi, Yaser M.; Battah, Mohammed M.; Halboup, Abdulsalam M.; Hassan, Hassan M. (Innovare Academic Sciences, 2021)
Objective: The objective of the current study was to evaluate the quality control parameters of seven brands of levofloxacin 500 mg film-coated tablet available in the Yemeni market. Methods: Physicochemical parameters assay was performed for seven brands of levofloxacin 500 mg film-coated tablet. Each brand was subjected to official and unofficial in vitro quality control tests, including weight variation, thickness, hardness, friability, disintegration, dissolution, and content uniformity assay by High-Performance Liquid Chromatography (HPLC). Results: Out of seven, six brands of levofloxacin 500 mg film-coated tablet passed official specified assay tests according to the United States Pharmacopeia (USP) specifications. They showed a similar profile of thickness ranged between0.01 and 0.10%, friability ranged between 0.01% and 0.34%, disintegration time ranged between 3.00 and 15.00 min, dissolution percentage ranged between 90.650 and 103.05 and content uniformity ranged between 93.62 and 107.12%. Regarding weight variation and hardness, six brands passed the weight variation test and only three brands showed optimum range (10-20 kg) of hardness test. Only one brand failed to pass the weight variation test, and four brands failed to pass the optimum range (10-20 kg) of hardness. Conclusion: There are no remarkable differences between the seven brands regarding in vitro quality control tests of content uniformity, thickness, friability, disintegration, and dissolution. Even though four brands were above the optimum range of hardiness, they showed complete disintegration and dissolution within the acceptable limit. Regular assessment of marketed drugs is required to ensure bioequivalent to their innovators.